Spin polarization in semimagnetic semiconductor two barrier spin filters - Lev, S.B.; Sugakov, V.I.; Vertsimakha, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The spin-dependent tunneling of electrons through the CdMgTe-based twobarrier
resonant tunneling system with a semimagnetic CdMnTe well is studied. The
level splitting in the semimagnetic well under an external magnetic field, caused by giant
Zeeman splitting, allows one to achieve a high level of spin polarization of the current
flowing through the spin filter. The current polarization degree depending on different
parameters of the system such as the carrier density, concentration of magnetic ions,
temperature, and the strength of the external magnetic and electric fields is analyzed.